Optimization of Electro-Optic Sampling by Photodiode's Choice for Terahertz Detection - Rizal, Fauzul; Benabdelghani, Imene (Universitas Negeri Malang, 2023)
Despite being widely used in a lot of measurements involving the generation of electromagnetic radiation, most of the optimization of this EOS technique only focused on the detection crystal and nonlinear coefficient of the said crystal. After the detection crystal, the combined pump-probe beam should be separated again based on its polarization and measured simultaneously with photodiodes. The authors found out that there are not many studies focusing on this part of the EOS technique and decided to present in this paper to contribute to the better optimization of detection with the EOS technique. We found out that the change of photodiode could have a relationship with the detected signal’s shape in the time and space domain, alongside the change of delay-time detection.